PENGARUH FINANCIAL EARLY WARNING SIGNAL TERHADAP PERUBAHAN HARGA SAHAM PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - TITA DETIANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
This research was performed to investigate the influence of Incured Loss Ratio, Liabilities to Liquid Aseet Ratio, Ratio agents balance to surplus,Premi Growth ratioon Stock Price at assurance on Indonesia Stock Exchange.The sample of this research was selected based on purposive sampling with the following criteria (1) assurance company published financial report during period 2005 till 2011; and (2) assurance company reported earning during period. The Data was based on publicity Indonesian Capital Market Directory from 2005 to 2011. Sample was acquired of 9 companies. Data was analyzed with multi linier regression. Empirical evidence showed that there is influence of Incured Loss Ratio or rasio beban klaim, Liabilities to Liquid Aseet Ratio or Rasio Likuiditas, Ratio agents balance to surplus andPremi Growth ratio on Stock Price.